How are COVID‐19 knowledge and concern associated with practising preventive behaviours in Australian adults?. (26th July 2021) - Khalesi, Saman; Vandelanotte, Corneel; Thwaite, Tanya L.; Alley, Stephanie J.; Williams, Susan L.; To, Quyen G.; Fenning, Andrew S.; Stanton, Robert
Abstract: Objective : This study investigated the association between COVID‐19 prevention knowledge and concern and practising preventive behaviour in Australian adults. Methods : Using an online survey, knowledge of Australian COVID‐19 guidelines, concerns about pandemic impact, the practice of preventive behaviours, and sociodemographic variables (i.e. age, gender, information source) were measured. Bivariate analysis and linear regression models were used. Results : A total of 1, 491 participants (age 50.5 ±14.9 years, 32.3% males) completed the survey. Higher knowledge and concern scores were associated with a higher practice of preventive behaviour scores (βs:0.47 & 0.08 respectively, p<0.001). Older adults (>65 years) and women had higher knowledge and practice scores compared to their counterparts. Being younger (<45 years) and male were associated with a lower practice score (βs:‐0.88 & −2.52, respectively, p<0.001). Referring to public and government sources as primary sources of information was associated with a higher practice score (β:1.21, p<0.001). Conclusions : Government‐run campaigns appear to be effective in promoting preventive practices and achieving a high knowledge of COVID‐19 guidelines in Australian adults. Implications for public health : Public health strategies are required to promote the practice of preventive behaviour for COVID‐19 (or future pandemics), especially among men and younger adults using social media, given their wide use of these sources.